Avaliação de aditivo superplastificante modificado com silanos em pasta de cimento Portland - Lamari, Bruna Aparecida (2023)
The central theme of this work is the study of the performance of silanes in cementitious matrices in order to reduce the amount of superplasticizer additive use through the use of silanes. For this, pastes with a water/cement ratio of 0.186 were produced and the replacement of superplasticizer additives based on polycarboxylate esters by vinyltriethoxysilane silanes (VTES), n-(2-aminoethyl)-3- aminopropyltrimethoxysilane (APTMS) and methacryloxypropyltrimethoxysilane (MCPTMS), in amounts of 20% and 40%, in Portland cement pastes. Apparent specific mass, incorporated air content, mini-slump and hydration kinetics (evaluated by isothermal calorimetry up to 48 h) of the pastes were determined in the fresh state. Thus, in the hardened state, the compressive and flexural strength tests (7 and 28 days), apparent specific mass and absorption by immersion of the pastes were carried out. The results showed that the substitution of 20% and 40% of VTES and APTMS considerably reduced the workability and increased the air content of the pastes in relation to the reference. In contrast, the incorporation of 20% and 40% of MCPTMS did not significantly affect these properties. The addition of silane, for all analyzed samples, had a delaying effect on the hydration process, the maximum delay verified had a hydration peak in approximately 36 h for the 40% MCPTMS system and the minimum delay of 11 h for the 20% system VTES. The replacement of 20% and 40% by any of the silanes progressively reduced the flexural tensile strength at both 7 and 28 days. In the compressive strength, as well as in the tensile strength in flexion, there was a decrease in the results when compared to the reference, except for the MCPTMS, at 7 and 28 days. In immersion absorption, all samples showed high percentages of absorption and voids index when compared to the reference.